Analysis of Factors Influencing Learning Outcome of Clinical Learning Competency among Nursing Students in Indonesia: Literature Review: Clinical Learning, Learning Outcome, Clinical Competence, Nursing Students - Miming Oxyandi; Santhna Letchmi Panduragana; Faridah Mohd Said (Sahabat Publikasi Kuu, 2023)
The quality of clinical education and the generation of nursing resources in Indonesia are influenced by the success of achieving clinical nursing learning by students in clinical practice. Because clinical learning is an important stage in improving clinical competence for students to practice skills, increase knowledge and develop a professional spirit of students into an atmosphere of clinical trials to evaluate real cases. The purpose of this study was to analyze the factors that influence learning outcomes in clinical learning among nursing students in Indonesia. This study used the Literature review method by taking electronic database data sources, namely Google Schloar, Science Direct, PubMed and Garuda with articles published in 2017 to 2022 with the keywords Clinical Learning, Learning Outcome, Clinical Competence, Nursing Student. After selection and identification according to the inclusion criteria, 15 articles were reviewed. Based on the results of the analysis of 15 research articles reviewed. There are several factors that influence the learning outcomes of clinical competency learning for clinical nursing practice students in Indonesia, namely the application of clinical learning methods, the role of academic preceptors and clinical preceptors and factors from students (preceptees). Suggestion: it is hoped that students, academic preceptors and clinical preceptors can improve interpersonal relationships and communication optimally and determine effective learning methods to improve the Learning Outcome Of Nursing Clinical Practice.